FUNDUS IMAGING APPARATUS - MORISHIMA SHUNICHI; SAKAI JUN (2024)
To provide a new technique for acquiring a higher-quality image of the fundus of a subject eye at a low cost and with a simple configuration, without the need for advanced optical design.SOLUTION: A fundus imaging apparatus includes two or more curved mirrors, an illumination optical system, and an image sensor. The illumination optical system includes a slit with an aperture configured to be arranged at a fundus conjugate position that is optically approximately conjugate with the fundus of the subject eye and irradiates the fundus with the slit-shaped illumination light generated by emitting light from a light source to the slit via the two or more curved mirrors. The image sensor is configured to be arranged at the fundus conjugate position and receives the return light from the subject eye. At least one of both ends in the longer direction of the aperture is displaced in the shorter direction of the aperture with the longer direction passing through the aperture center as a reference.SELECTED DRAWING: Figure 1 【課題】高度な光学設計を必要とすることなく、低コスト、且つ、簡素な構成で、より高画質の被検眼の眼底の画像を取得するための新たな技術を提供する。【解決手段】眼底撮影装置は、２以上の曲面鏡と、照明光学系と、イメージセンサとを含む。照明光学系は、被検眼の眼底と光学的に略共役な眼底共役位置に配置されるように構成された開口が形成されたスリットを含み、光源からの光をスリットに照射することにより生成されたスリット状の照明光を２以上の曲面鏡を介して眼底に照射する。イメージセンサは、眼底共役位置に配置されるように構成され、被検眼からの戻り光を受光する。開口の長手方向の両端部の少なくとも一方は、開口中心を通る長手方向を基準として開口の短手方向に変位している。【選択図】図１